The Party's Over oil, war and the fate of industrial societies - Heinberg, Richard (Gabriola Island New Society Publishers, 2005)
The world is about to change dramatically and permenantly as a result of oil depletion.Within the next few years, the global production of oil will peak. Thereafter, even with a switch to alternative energy sources, industrial societies will have less energy available to do all the things essential to their survival. W e ar entering a new era as different from industrial one as the latter was from mediaeval times.
Includes bibliographical references (p. 287-294)
Keywords: Petroleum industry and trade